An MPP Monounary Algebra Induced by an Endomorphism of the Direct Product of Two Chains (European Journal of Pure and Applied Mathematics, 2025)
A finite modular lattice $A$ is said to be MPP if there is an endomorphism, called an MPP endomorphism, whose the pre-period is equal to the length of $A$. A monounary algebra $(A,f)$ is said to be MPP if $f$ is an MPP endomorphism of a lattice $\A$, called an MPP corresponding lattice to $(A,f)$. In this work, we show all MPP monounary algebras induced by endomorphisms of the direct products of two chains.
Keywords: Pre-period; Monounary algebra; Chain; Endomorphism